EFFECT OF THINNING OF DIFFERENT INTENSITY ON THE TAXATION PARAMETERS OF OAK STANDS IN FRESH FERTILE CONDITIONS - Lunachevskyi, L. S.; Lukyanets, V. A.; Musienko, S. I. (Forestry and Forest Melioration, 2018)
Introduction Environmental and economic aspects, which involve detection of biologically acceptable limits for increase of thinning intensity and frequency, should be taken into account during thinning systems development and implementation. Despite of significant scientific groundwork referring oak stands thinning, issues relating to their intensity and frequency remain disputable. Materials and Methods Research methodology included characteristics of oak stands by practical standards in forestry and forest inventory. Research conducted in the experiment on the effect of thinning intensity on the growth of artificial oak stands, laid by prof. P. P. Izyumsky and L. I. Kurylo in 1954 at 28 years old stands in “Zhovtneve Forest Economy” of Merchanske Forestry (planning compartments 57 and 58). Forest plantations were created using oak and maple with mixing pattern of 1 row of oak and 1 row of Norway maple. In sections 7 and 8, common ash is presented in maple rows. Results The results of 55 years research of thinning effect on dynamics of taxation parameters of artificial oak stands in fresh fertile conditions of southern Forest-Steppe are given. It was found that plantations after moderate and intense thinning of the canopy have better height and diameter growth and are more productive than oak stands with low intensity of thinning. However, in areas where intense thinning is carried out, the health of plantation and timber quality are slightly worse than in stands after moderate thinning. Intense stand thinning results in water shoots on the oak trunks and dieback of trees, which determines the lower wood quality. Distribution of oak trees by sanitary condition classes in sections with varying intensity of thinning indicates a significant number of trees of IV and VI sanitary condition classes at all sections of the experiment. Their share in the stand depending on the variant is from 14.7 % (section 2) to 21.9 % (control). Sanitary condition index of the stand varies from 2.18 (Section 2) to 2.54 (control) that characterizes plantations as weakened (sections 2, 4, 7) and very weakened (control section 5). A significant number of partially dried out and dead oak trees in all sections and the presence of suppressed and stunted trees greatly worsen the sanitary condition of planting. Therefore, to improve the plantations state in research objects it is necessary to carry out increment thinning. Conclusions Mixed stands with high forest productivity and high stand density are formed in artificial oak-maple plantations. In such plantations, even high intensive tending felling allows formation of approaching maturity stands of the 1st class of forest productivity with stand density of about 0.8. Among the experimental variants, a moderate thinning of the oak stands showed the best results.